Efektivitas Edukasi Asi Eksklusif melalui Whatsapp Group Terhadap Pengetahuan, Sikap dan Dukungan Suami - Herianti Herianti; Vevi Gusnidarsih; Musdalipa Musdalipa; Ade Elvina; Resya Aprillia; Dea Lestari (Malahayati Nursing Journal, 2026)
ABSTRACT Exclusive breastfeeding is the provision of breast milk alone, without any other food additives from birth until the baby is 6 months old. Breast milk contains all the nutrients, fluids and immunity that babies need to fulfill their nutritional needs in the first 6 months. The Indonesian government has set a target of 80% coverage of exclusively breastfed infants as stipulated. Based on data from the Bengkulu City Health Profile Book, the highest coverage of exclusively breastfed infants in the Beringin Raya Health Center working area was 96.3% while the lowest was 17.1% in the Sawah Lebar Health Center working area. The purpose of this study was to determine the benefits of implementing exclusive breastfeeding education through whatsapp groups on the knowledge and attitudes of pregnant women and husband support (wife's perception) in the working area of the Sawah Lebar Health Center, Bengkulu City. This type of research uses the Quasi Experiment method with a one group pre test-post test design. The sample of this study was pregnant women TM III totaling 30 people using purposive sampling technique. Data analysis used in the study using Wilcoxon test and Paired Sample T Test. The results obtained the average knowledge of pregnant women before 6.00 and after 7.73, the average attitude of pregnant women before 29.40 and after 31.32 and the average husband's support before 5.60 and after 7.30. The results of the Wilcoxon signed rank test obtained a p value of knowledge of 0.00 (p 0.05), a p value of attitude of 0.00 (p 0.05), a p value of husband support of 0.00 (p 0.05) showed that there was an increase in knowledge and attitudes of pregnant women and husband support (wife's perception) before and after being given exclusive breastfeeding education through whatsapp groups in the working area of the Sawah Lebar Health Center, Bengkulu City. Keywords: Exclusive Breastfeeding Education, Whatsapp Group, Pregnant Women TM III, Knowledge, Attitude, Husband Support.  ABSTRAK Meskipun ASI eksklusif memberikan banyak manfaat bagi bayi dan pemerintah Indonesia menetapkan target cakupan bayi mendapat ASI eksklusif yaitu sebesar 80%, tetapi nyatanya cakupan bayi yang mendapat ASI eksklusif masih rendah. Data cakupan pemberian ASI eksklusif di Provinsi Bengkulu tahun 2022 sebesar 64,4%, dimana cakupan bayi yang mendapat ASI eksklusif terendah di wilayah kerja Puskesmas Sawah Lebar yaitu 17,1%. Tujuan penelitian ini untuk mengetahui manfaat penerapan edukasi ASI eksklusif melalui whatsapp grup terhadap pengetahuan, sikap dan dukungan suami (persepsi istri) di wilayah kerja Puskesmas Sawah Lebar Kota Bengkulu. Penelitian ini menggunakanQuasi Eksperimen dengan rancangan one group pre test-post test design. Sampel penelitian yaitu ibu hamil TM III yang berjumlah 30 orang. Teknik sampling menggunakan purposive sampling. Analisis data univariat menggunakan uji shipor wilk dan analisis bivariat dengan menggunakan uji Wilcoxon dan Paired Sample T Test. Diperoleh nilai mean pre test pengetahuan ibu hamil sebesar 6,00 dan nilai mean post test sebesar 7,73, nilai mean pre test sikap ibu hamil sebesar 29,40 dan nilai mean post test sebesar 31,32 dan nilai mean pre test dukungan suami sebesar 5,60 dan nilai mean post test sebesar 7,30. Analisis data dari hasil uji Wilcoxon signed rank test diperoleh nilai p value pengetahuan 0,00 (p 0,05), nilai p value sikap 0,00 (p 0,05) dan nilai p value dukungan suami  0,00 (p 0,05) artinya secara statistic menunjukan hasil yang signifikan. Ada peningkatan pengetahuan, sikap dan dukungan suami (persepsi istri) sebelum dan sesudah diberikan edukasi ASI eksklusif melalui whatsapp grup di wilayah kerja Puskesmas Sawah Lebar Kota Bengkulu Tahun. Kata Kunci: ASI Eksklusif, Whatsapp Grup, Ibu Hamil TM III, Pengetahuan, Sikap, Dukungan Suami.